2020
DOI: 10.1029/2020jd033579
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Variability and Tendencies in Middle Atmosphere Temperature and Zonal Wind From WACCM6 Simulations During 1850–2014

Abstract: Long-term variability of middle atmosphere temperature (T) and zonal wind (U) is investigated using a three-member ensemble of historical simulations of NCAR's Whole Atmospheric Community Climate Model latest version 6 (WACCM6) for 1850-2014 (165 years). The model reproduces the climatological features of T and U. The contributions of Quasi Biennial Oscillation (QBO) at 10 and 30 hPa, solar cycle (SC), El Niño-Southern Oscillation (ENSO), ozone depleting substances (ODS), carbon dioxide (CO 2), and stratospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 57 publications
6
46
3
Order By: Relevance
“…Given that background, it is unlikely the symmetric Q10DW‐W1 observed in 2019 Southern SSW is a NM since the equivalent depth for the symmetric Q10DW‐W1 is too short to be amplified as a resonant oscillation mode in the middle atmosphere. The mean temperature required to result in such a NM translates to an equivalent depth of 2.5 km for the symmetric Q10DW‐W1 is 61 K, which is ∼100 K lower than the expected mean temperature in the middle atmosphere during the austral summer (Ramesh et al., 2020). This result suggests that there is more likely a forcing mechanism to excite the upward propagating symmetric Q10DW‐W1 observed during the 2019 SSW.…”
Section: Resultsmentioning
confidence: 91%
“…Given that background, it is unlikely the symmetric Q10DW‐W1 observed in 2019 Southern SSW is a NM since the equivalent depth for the symmetric Q10DW‐W1 is too short to be amplified as a resonant oscillation mode in the middle atmosphere. The mean temperature required to result in such a NM translates to an equivalent depth of 2.5 km for the symmetric Q10DW‐W1 is 61 K, which is ∼100 K lower than the expected mean temperature in the middle atmosphere during the austral summer (Ramesh et al., 2020). This result suggests that there is more likely a forcing mechanism to excite the upward propagating symmetric Q10DW‐W1 observed during the 2019 SSW.…”
Section: Resultsmentioning
confidence: 91%
“…There is a trend in the NINO3.4 index in the most recent decades that is consistent with an overall warming in the ocean temperature. More details on the predictors can be obtained from Ramesh et al (2020).…”
Section: Resultsmentioning
confidence: 99%
“…The regression analysis attributes the long-term increase in DW1 amplitude mainly to increasing trend in CO 2 . However, as shown in Ramesh et al (2020), a complete separation of trends due to CO 2 and EESC is not possible because of similarities in the time series of forcing. Although the stratospheric aerosols (AOD) have negligible impact on global mean tidal amplitudes, they show negative contribution in all the three components for E23 with slightly larger effect on U 24 than V 24 .…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
See 1 more Smart Citation
“…This scaling choice allows the regression results interpreted as the change in the winds given a change in the index from its minimum to maximum value (whilst allowing for outliers). Ramesh et al (2020). Finally, Ford et al (2009) and Ramesh et al (2020) found links between the MLT and QBO.…”
Section: Climate Indicesmentioning
confidence: 91%